2017
DOI: 10.3390/ma10080862
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Disorder-Driven Metal–Insulator Transition in Crystalline Vacancy-Rich GeSbTe Phase-Change Materials

Abstract: Metal–insulator transition (MIT) is one of the most essential topics in condensed matter physics and materials science. The accompanied drastic change in electrical resistance can be exploited in electronic devices, such as data storage and memory technology. It is generally accepted that the underlying mechanism of most MITs is an interplay of electron correlation effects (Mott type) and disorder effects (Anderson type), and to disentangle the two effects is difficult. Recent progress on the crystalline Ge1Sb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 128 publications
0
26
0
Order By: Relevance
“…with disordered vacancies possess insulating behavior. [60][61][62] Thus, control of disorder in phase change materials is very important for the application. Therefore, it is essential to reveal the local structure of relevant phases of the alloys.…”
Section: Introductionmentioning
confidence: 99%
“…with disordered vacancies possess insulating behavior. [60][61][62] Thus, control of disorder in phase change materials is very important for the application. Therefore, it is essential to reveal the local structure of relevant phases of the alloys.…”
Section: Introductionmentioning
confidence: 99%
“…The prototypical PCM material Ge 2 Sb 2 Te 5 (GST) has been intensively studied in the past a few years 46 . A lot of work have been done for the understanding of carrier transport due to its great importance for the crystalline state of PCM 7 . It has been reported that metal-insulator transition (MIT) upon annealing can be observed in crystalline GeSbTe compounds, and the Anderson localization resulted from the vacancy disorder is responsible for this MIT 810 .…”
Section: Introductionmentioning
confidence: 99%
“…The transmission contrast in the NIR region between the amorphous phase and the crystalline phase and the rapid reversibility of Ge-Sb-Te alloys [42] can be used to design a reversible NIR transmission window [12]. It is clear from Figs.…”
Section: Resultsmentioning
confidence: 99%